Peran UMKM Dalam Mengurangi Tingkat Pengangguran Masyarakat Di Era Vuca - Indrawan Syah; Wahyu Eko Pujianto (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
MSMEs are one way to improve the economy in a country, especially Indonesia. UMKM is a business that can survive in all conditions. In its development, UMKM has one of the benefits of reducing unemployment. This study uses a qualitative method supported by a literature review. This study aims to analyze one of the SMEs in Indonesia, especially in the Sidoarjo sub-district in the Banana Aroma Various Flavor business. Where the results of this research were obtained by the presence of UMKM Aroma Aneka Rasa bananas which can reduce unemployment rates.